2016
DOI: 10.1093/cercor/bhw207
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Hes-1 Concomitant with its Differential Activation Mediates Neural Stem Cell Maintenance and Radial Glial Propensity in Developing Neocortex

Abstract: Notch signaling pathway and its downstream effector Hes-1 are well known for their role in cortical neurogenesis. Despite the canonical activation of Hes-1 in developing neocortex, recent advances have laid considerable emphasis on Notch/CBF1-independent Hes-1 (NIHes-1) expression with poor understanding of its existence and functional significance. Here, using reporter systems and in utero electroporation, we could qualitatively unravel the existence of NIHes-1 expressing neural stem cells from the cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Previous studies have shown neurogenesis to be enhanced by TGFβ (Mathieu et al, 2010) and by TGFβ+ activated microglia in the context of neurodegeneration (De Lucia et al, 2016). In addition, TGFβ has been identified as a factor inducing Notch-independent HES-1 signalling (Chacón and Rodríguez-Tébar, 2012), which would specifically contribute to the maintenance of a primitive neural stem cell pool (Dhanesh et al, 2017). This would support the idea that, as for acute ECS, chronic treatment would tend to increase the activity of the innate immune system and simultaneously contribute to proliferative neurogenic processes 4 h later.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown neurogenesis to be enhanced by TGFβ (Mathieu et al, 2010) and by TGFβ+ activated microglia in the context of neurodegeneration (De Lucia et al, 2016). In addition, TGFβ has been identified as a factor inducing Notch-independent HES-1 signalling (Chacón and Rodríguez-Tébar, 2012), which would specifically contribute to the maintenance of a primitive neural stem cell pool (Dhanesh et al, 2017). This would support the idea that, as for acute ECS, chronic treatment would tend to increase the activity of the innate immune system and simultaneously contribute to proliferative neurogenic processes 4 h later.…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in Hes-1 impairs differentiation and cell proliferation in the epidermis and hair follicles and reduces the pluripotency of stem cells in the skin [ 87 ]. In hair follicles, the expression of the target gene Hes-1 may be related to changes in Jagged-1 ligand gene expression [ 88 ]. Studies have found that reduced Hes-1 expression limits the ligand–receptor interaction and reduces Hes-1 signaling [ 89 ].…”
Section: Reviewmentioning
confidence: 99%
“…NICD also controls NF-kß expression through Hairy and enhancer of split1 (Hes1)(Espinosa et al, 2010). This protein controls neurogenesis and it has been shown to be expressed following a cyclic pattern during certain stages of development(Dhanesh et al, 2016) as well as it occurs with miR-29a. Moreover, miR-29a controls Nuclear factor I A (Nfia) expression, a transcription factor repressor of Hes1 expression(Liu et al, 2015).…”
mentioning
confidence: 99%